Pengaruh Kualitas Produk Dan Layanan Terhadap Kepuasan Konsumen (Studi kasus pada Café Sore di Kabupaten Bone) - Ahmad Rifqi; Ismail Keri; Muh. Arafah (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to determine the effect of product quality and service on consumer satisfaction at Café Sore in Bone Regency (1). This study uses a quantitative approach with a survey method to 100 respondents. The data analysis technique uses multiple linear regression through the help of SPSS software (2). The results of the study indicate that product quality (X1) has a significant effect on consumer satisfaction with a significance value of 0.011 <0.05 (3). Service (X2) also has a significant effect with a significance value of 0.000 <0.05. The F test shows that both independent variables simultaneously affect consumer satisfaction (Y) with a significance of 0.000 and F count 79.872> F table 3.09 (4). In conclusion, both product quality and service partially and simultaneously have a significant effect on the level of consumer satisfaction (5)..